Inflation in the West African countries: The impact of cocoa prices, budget deficits, and migrant remittances - Adusei Jumah; Robert M. Kunst (Institute for Advanced Studies (IHS), 2007)
We verify whether cocoa prices could be a source of inflation in five countries of the West African region within a framework that includes other variables such as migrant remittances to the region and a fiscal policy variable represented by the government budget deficit. Unlike earlier studies that explicitly use money supply variables, the inclusion of migrant remittances enables us to examine the effect of an international capital flow variable on inflation. The results reveal that the influence of cocoa prices on consumer price inflation is strong and statistically significant. The influence of the budget deficit and the flow of migrant remittance variables on inflation are, however, weak.
Keywords: C5; E31; 330; inflation; West Africa; cocoa; budget deficits; remittances; Kakao; Preis; Inflation; Öffentliche Schulden; Rücküberweisung (Migranten); Schätzung; Westafrika